Between Allah & Jesus : what Christians can learn from Muslims - Kreeft, Peter (Downers Grove, Ill. : IVP Books, 2010)
'What would happen if Christians and a Muslim at a university talked and disagreed, but really tried to understand each other? What would they learn? That is the intriguing question Peter Kreeft seeks to answer in these imaginative conversations on issues ranging from prayer and worship to evolution and abortion, from war and politics to the nature of spiritual struggle and spiritual submission.'--BOOK JACKET.
Introduction -- On comparative religions -- On Islam vs. the West -- On Jesus and Muhammad -- On the relation between morality and theology -- On surrender -- On loving God and fearing God -- On who goes to heaven -- On liberals and conservatives -- On prayer and the wildness of God -- On feminism -- On sexual morality and moral ambiguity -- On Islam and politics -- On war and pacifism -- On Jihad and enemies -- On evolution and sex -- On abortion and compassion -- Conclusion.
Keywords: Islam -- Relations -- Christianity; Christianity and other religions -- Islam; Islam -- Doctrines; Dogma